2010
DOI: 10.1093/pcp/pcq060
|View full text |Cite
|
Sign up to set email alerts
|

Three PsbQ-Like Proteins are Required for the Function of the Chloroplast NAD(P)H Dehydrogenase Complex in Arabidopsis

Abstract: Arabidopsis has three PsbQ-like (PQL) proteins in addition to the PsbQ subunit of the oxygen-evolving complex of PSII. Recent bioinformatic and proteomic studies suggested that the two PQL proteins, PQL1 (At1g14150) and PQL2 (At3g01440), might function in the chloroplast NAD(P)H dehydrogenase (NDH) complex; however, their molecular function has not been characterized. In this study, we examined the function of the chloroplast NDH in the Arabidopsis pql1 and pql2 mutants. Post-illumination increases in Chl fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 36 publications
8
66
0
Order By: Relevance
“…1C). So far, a total of 25 NDH subunits have been identified by various approaches (Rumeau et al, 2005;Ishihara et al, 2007;Ishikawa et al, 2008;Majeran et al, 2008;Shimizu et al, 2008;Peng et al, 2009;Sirpiö et al, 2009aSirpiö et al, , 2009bTakabayashi et al, 2009;Suorsa et al, 2010;Yabuta et al, 2010). If we assume that only one copy of each subunit is included in the complex, the calculated molecular mass of NDH is approximately 690 kD, which is almost identical to that of the NDH complex detected in lhca5 lhca6.…”
Section: Ndh Is Present As a Monomer In The Lhca5 Lhca6 Double Mutantmentioning
confidence: 84%
“…1C). So far, a total of 25 NDH subunits have been identified by various approaches (Rumeau et al, 2005;Ishihara et al, 2007;Ishikawa et al, 2008;Majeran et al, 2008;Shimizu et al, 2008;Peng et al, 2009;Sirpiö et al, 2009aSirpiö et al, , 2009bTakabayashi et al, 2009;Suorsa et al, 2010;Yabuta et al, 2010). If we assume that only one copy of each subunit is included in the complex, the calculated molecular mass of NDH is approximately 690 kD, which is almost identical to that of the NDH complex detected in lhca5 lhca6.…”
Section: Ndh Is Present As a Monomer In The Lhca5 Lhca6 Double Mutantmentioning
confidence: 84%
“…More recent studies have also confirmed that PPL2 (17 kD) is a novel subunit associated with the NDH complex in Arabidopsis (Peng et al, 2009;Suorsa et al, 2009). In addition, several PsbQ-like (PQL) proteins (including PsbQ-F1 and PsbQ-F2, both 17 kD) have been shown to be necessary for the function of the NDH complex in Arabidopsis (Majeran et al, 2008;Peng et al, 2009;Suorsa et al, 2009;Yabuta et al, 2010). Furthermore, PQL1 and PQL2 were found to be tightly associated with the NDH-PSI supercomplex (Suorsa et al, 2010;Yabuta et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with Arabidopsis and tobacco have shown that failure to form an active chloroplast NDH complex results in a characteristic change in the kinetics of Chl fluorescence in response to darkening , Rumeau et al, 2005, Munshi et al, 2006, Ishihara et al, 2007, Ishikawa et al2008, Peng et al, 2009, Takabayashi et al, 2009, Suorsa et al, 2010, Yabuta et al, 2010. Figure 2 compares this light-dark transient for the maize mutants ZmNdho and ZmNdhn and respective normal sibling controls.…”
Section: Fundamental Properties Of Ndh-deficient Maize and Arabidopsismentioning
confidence: 96%
“…At least 11 plastid and 25 nuclear genes encode NDH subunits and related protein factors in Arabidopsis (Ifuku et al, 2011. Serial disruption of several nuclear genes encoding structural subunits or assembly factors resulted in failed NDH supercomplex assembly and disrupted electron flow to PQ (plastoquinone) in the dark (Rumeau et al, 2005, Munshi et al, 2006, Ishihara et al, 2007, Ishikawa et al, 2008, Takabayashi et al, 2009, Peng et al, 2010, Suorsa et al, 2010, Yabuta et al, 2010, Armbruster et al, 2013. Chloroplastic NDH has been assigned to a redundant NAD(P)H-dependent PSI cyclic electron transport pathway in C 3 plants (Nixon 2000).…”
mentioning
confidence: 99%